2015
DOI: 10.1039/c4nr07005d
|View full text |Cite
|
Sign up to set email alerts
|

Photoluminescent graphene quantum dots for in vivo imaging of apoptotic cells

Abstract: Apoptosis (programmed cell death) is linked to many incurable neurodegenerative, cardiovascular and cancer causing diseases. Numerous methods have been developed for imaging apoptotic cells in vitro; however, there are few methods available for imaging apoptotic cells in live animals (in vivo). Here we report a novel method utilizing the unique photoluminescence properties of plant leaf-derived graphene quantum dots (GQDs) modified with annexin V antibody (AbA5) to form (AbA5)-modified GQDs (AbA5-GQDs) enablin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(43 citation statements)
references
References 39 publications
1
42
0
Order By: Relevance
“…Recently, Roy et al developed a novel method using NG modified with Annexin V antibody (AbA5) to form (AbA5)-modified NG (AbA5-NG) enabling to label apoptotic cells in live zebrafish (Danio rerio) [ 69 ]. Zebrafish showed bright red photoluminescence in the presence of apoptotic cells.…”
Section: Biosensing Cancer Biomolecules or Cellsmentioning
confidence: 99%
“…Recently, Roy et al developed a novel method using NG modified with Annexin V antibody (AbA5) to form (AbA5)-modified NG (AbA5-NG) enabling to label apoptotic cells in live zebrafish (Danio rerio) [ 69 ]. Zebrafish showed bright red photoluminescence in the presence of apoptotic cells.…”
Section: Biosensing Cancer Biomolecules or Cellsmentioning
confidence: 99%
“…4 In addition, the graphene structure inherent in GQDs endows them with some of the unusual properties of graphene. For these reason, GQDs are proposed to be applicable in various fields, such as biological imaging, [9][10][11] sensing, 12 drug delivery, 13 catalysis, 14,15 and photovoltaics. 16 The strategies for the preparation of GQDs can be divided into two major categories: top-down and bottom-up approaches.…”
Section: Introductionmentioning
confidence: 99%
“…[ 14 , 15 ] Recent studies showed that the surface-modified nanoparticles can penetrate into the apoptotic cells, shedding light on the new field of CDots application. [ 16 , 17 ] Also, the ability to visualize model membranes [ 18 ] and cells [ 19 , 20 ] with carbon dots was shown. Meantime, in our knowledge, there were no attempts to apply carbon nanoparticles to visualize the changes of cell functional states, such as apoptosis.…”
Section: Introductionmentioning
confidence: 99%